Discovering Hawaii. - Questar, Inc. ([New York, NY] : Questar, 2001)
Enter Kilauea and other legendary volcanoes. Hear the story of Hawaii's great warrior-king, Kamehameha. Share in the fun of Waikiki Beach and Lahaina, then catch an aerial view of the vast canyon lands of Kauai. Learn about Hawaiian customs and folklore, while Sea Life Park stages some amazing shows with porpoises, whales, and other crowd pleasers. Surfing, snorkeling, cliff diving--Hawaii has it all!
Program chapters: Hawaii -- Early settlers -- Maui -- Resort areas -- Hula dancing -- Molokai -- Father Damien -- Oahu -- Cultural Center -- Cliff diving -- Pearl Harbor -- Kauai. DVD extras: Early inhabitants -- Voyages of Captain Cook -- The 20th century.
Title from container.
Videography by Stan Kibby and GLE, Inc. ; edited by Barry Schienberg [and others] ; music composition by Tim Gennert.
Narrator: Frank Gorin.
MPAA rating: Not rated.
DVD.
107971
Keywords: Travel; Hawaii -- Description and travel; Travelogues (Motion pictures, television, etc.); Educational films; DVD-Video discs; Videodiscs; DVDs